2018
DOI: 10.3390/en11061607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Vertical Electric Field on the Surface Flashover Characteristics of a Bushing Model

Abstract: High-voltage bushings play a crucial role in energy conveyance. Their specialized electric structure makes the bushing more vulnerable to surface discharge. However, the influence of a vertical electric field on the surface flashover of bushing structures remains unclear. To investigate this mechanism, four simplified bushing samples were built and the influence of pollution, leakage length, and the electric field component vertical to the dielectric surface on flashover properties of the bushing samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The progression of the arc propelled by the electric field along the surface. Prior investigations conducted within our research group [25,26] have effectively elucidated the mechanism through which electric fields propel the development of arcs along the surface. A succinct summary of this mechanism is provided below, serving to enhance the reader's comprehension of the subsequent model detailing the transition from pollution arc to sliding arc.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the arc propelled by the electric field along the surface. Prior investigations conducted within our research group [25,26] have effectively elucidated the mechanism through which electric fields propel the development of arcs along the surface. A succinct summary of this mechanism is provided below, serving to enhance the reader's comprehension of the subsequent model detailing the transition from pollution arc to sliding arc.…”
Section: Discussionmentioning
confidence: 99%
“…Krile et al revealed a material dependence on the discharge path of the surface flashover along dielectric insulators in SF6 environment [16]. The electric field also has an important influence on the surface flashover of dielectric insulators [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Yimin, Baoji, Fengjing etc. HVDC converter stations in China have repeatedly experienced internal breakdown failures on resin impregnated paper (RIP) valve side bushing caused by current heating, resulting in single-pole lockout at the HVDC converter stations, which has large negative impact on the AC-DC transmission system [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%